Building on purposive interpretation outcomes to discern occupational practices from interview-to-the-double results - Ayaya, Onesmus (Journal of Management and Business Education, 2024)
Studies leading to revised teaching and learning in business have relied on survey questionnaires without recognising multi-party data collection and evaluation procedures. The study demonstrates how the interview-to-the-double (ITTD) approach builds on the purposive interpretation (PI) results in documenting regulated occupation practices to discern a qualification framework. Recent arguments have been made to develop business rescue practitioner capabilities through short skills development programmes (SSDPs) as continuing professional development (CPD) mechanisms. The advocacy for the use of SSDPs to develop practitioner talent in the field recognises the limitations of prior development of practitioners. The study employed the ITTD, a qualitative inquiry approach promoting practice theory, to obtain results on occupational practices in a regulated environment with 11 professional organisations. The occupational practices determine the occupation’s teaching and learning outcomes. The results and conclusions are based on ITTD data collected from practitioner sessions. The practice theory’s tenets guided the assessment of the opportunities to build the ITTD data collection procedures on PI results to document occupational practices needed for the learning and development of business rescue practitioners. The findings show that business rescue practitioners have 11 categories of occupational tasks constituting occupational areas of corporate renewal work. The investigation argues that corporate renewal or rehabilitation practices are unified, outcome-oriented, and enacted practices requiring a distinct competency framework. The paper argues that the ITTD approach can methodically verify occupation practices premised on legal prescripts. The study verified occupational tasks traceable to specific training disciplines not addressed in the SSDPs or in the previous practitioner training. The study illustrates the opportunities to build ITTD procedures on purposive PI results to address problems associated with surveys in practice documentation in the management curriculum development. The rush to use survey instruments to make a case for occupation-specific learning and development programmes provides misleading results if the PI and ITTD-generated data do not complement results from survey procedures. Documenting practices in a regulated occupation requires multiple data collection approaches to determine learning competencies.